(3eHGOF GdEbJUGO GdLRFj (B/s - (3Hfj gGfj, YHO GdQRGb MSjf Ydjs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2013)
(3fXQjI GdWdH hGdYQV(B- (3GdeQhfI(B- (3fXQjI GdefaYI hJhGRf GdeSJgdc(B- (3GdefTCI hcdaI GdEfJGL(B- (3GdefTCI aj GdShb GdJfGaSjI(B- (3GdefTCI aj Shb GdEMJcGQ(B- (3GdefGaSI ZjQ GdJGeI(B- (3GMJcGQ GdbdI(B- (3JhXja YhGed GdEfJGL(B- (3GMJcGQ GdTQGA(B- (3GMJcGQ GdbdI aj GdTQGA(B- (3JMOjO SYQ eONd GdGfJGL(B- (3ehVhYGJ eNJGQI aj GdEbJUGO GdLRFjs
(3eYLe GdeUWdMGJ GdEbJUGOjI hGdGSeGA hGdCacGQ GdeJUdI HgG U(B.369s
Keywords: (3GdCShGbs; (3GdEbJUGOs; (3GdEbJUGO GdLRFjs